2021
DOI: 10.3390/ijerph18168599
|View full text |Cite
|
Sign up to set email alerts
|

Post-Lockdown Effects on Students’ Mental Health in Romania: Perceived Stress, Missing Daily Social Interactions, and Boredom Proneness

Abstract: The rapid spread of COVID-19 worldwide was accompanied by intense fears, confusion, worries, anger, and stress threatening people’s mental health. Unprecedented measures to slow down and prevent the transmission of COVID-19 have had various impacts on the population’s health behaviour and mental health. The main purpose of the present study is to investigate the lockdown’s effects on university students’ mental health in Romania. Based on a cross-sectional design, the survey data were collected from a sample o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 90 publications
1
20
0
Order By: Relevance
“…In agreement with the literature, women ( Dumitrache et al, 2021 ) and younger students ( Shanahan et al, 2020 ) have an increased risk of psychological distress. Financial difficulties are the major risk factor for psychological distress in our study (OR = 4.58 for important difficulties), consistent with previous data ( Rajapuram et al, 2020 ).…”
Section: Discussionsupporting
confidence: 90%
“…In agreement with the literature, women ( Dumitrache et al, 2021 ) and younger students ( Shanahan et al, 2020 ) have an increased risk of psychological distress. Financial difficulties are the major risk factor for psychological distress in our study (OR = 4.58 for important difficulties), consistent with previous data ( Rajapuram et al, 2020 ).…”
Section: Discussionsupporting
confidence: 90%
“…For depressive-related symptomatology, the Patient Health Questionnaire (PHQ-9) scale was adopted [19], assessing the severity of depressive symptoms during the previous two weeks. Among a range score from 0 to 27, the severity could be assessed as normal (0-4), ( 2) mild (5-9), ( 3) moderate (10)(11)(12)(13)(14), (4) moderate/severe (15)(16)(17)(18)(19), and severe (20)(21)(22)(23)(24)(25)(26)(27).…”
Section: Survey Questionnairementioning
confidence: 99%
“…COVID-19 significantly contributed to changed working habits too, with an increased adoption of working solutions that transformed home environments into work environments. In the scientific literature, several studies have highlighted the impact of COVID-19 and the lockdowns on the mental health and depression of students, one of the most fragile demographics of the population [ 20 , 21 , 22 ]. Nevertheless, the role of the housing environment where most of them spent their daily hours was rarely considered [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…This is important to our research, as previous studies showed that social media use and cyber engagement amplifies cyberbullying, cyber harassment and cyber stalking (Al-Rahmi et al, 2018). The time spend online has increased following the 2020 lockdown (Dumitrache et al, 2021), and as the pandemic pushed classes online, as did the communication between the students and their professors and colleagues. This increase in online communication made students more vulnerable to cyberbullying.…”
Section: The Way Students Use the Internetmentioning
confidence: 99%